Direct Base-Assisted C‒H Cyclonickelation of 6-Phenyl-2,2′-bipyridine - Vogt, Nicolas; Sivchik, Vasily; Sandleben, Aaron; Hörner, Gerald; Klein, Axel (Molecules (Basel, Switzerland), 2020)
The organonickel complexes [Ni(Phbpy)X] (X = Br, OAc, CN) were obtained for the first time in a direct base-assisted arene C(sp2)–H cyclometalation reaction from the rather unreactive precursor materials NiX2 and HPhbpy (6-phenyl-2,2′-bipyridine) or from the versatile precursor [Ni(HPhbpy)Br2]2. Different from previously necessary C‒Br oxidative addition at Ni(0), an extended scan of reaction conditions allowed quantitative access to the title compound from Ni(II) on synthetically useful timescales through base-assisted C‒H activation in nonpolar media at elevated temperature. Optimisation of the reaction conditions (various bases, solvents, methods) identified 1:2 mixtures of acetate and carbonate as unrivalled synergetic base pairs in the optimum protocol that holds promise as a readily usable and easily tuneable access to a wide range of direct nickelation products. While for the base-assisted C‒H metalation of the noble metals Ru, Ir, Rh, or Pd, this acetate/carbonate method has been established for a few years, our study represents the leap into the world of the base metals of the 3d series.